Frommer's San Francisco 2006 - Lenkert, Erika (New Jersey, 2005)
You'll never fall into the tourist traps when you travel with Frommer's. It's like having a friend show you around, taking you to the places locals like best. Our expert authors have already gone everywhere you might go- they've done the legwork for you, and they're not afraid to tell it like it is, saving you time and money. No other series offers candid reviews of so many hotels and restaurants in all price ranges. Every Frommer's Travel Guide is up-to-date, with exact prices for everything, dozens of color maps, and exciting coverage of sports, shopping, and nightlife. You'd be lost without
Keywords: California San Francisco; Guidebooks